Miniaturized Dual-band Antenna Array with Double-negative (DNG) Metamaterial for Wireless Applications - Alqadami, Abdulrahman Shueai Mohsen; Mohd Faizal, Jamlos; Ping, Jack Soh; Sharul Kamal, Abdul Rahim; Vandenbosch, Guy A. E.; Narbudowicz, Adam (Springer, 2017)
A miniaturized dual-band antenna array using a negative index metamaterial is presented for WiMAX, LTE, and WLAN applications. This left-handed metamaterial plane is located behind the antenna array, and its unit cell is a combination of split-ring resonator, square electric ring resonator, and rectangular electrical coupled resonator. This enables the achievement of a metamaterial structure exhibiting both negative permittivity and permeability, which results in antenna size miniaturization, efficiency, and gain enhancement. Moreover, the proposed metamaterial antenna has realized dual-band operating frequencies compared to a single frequency for normal antenna. The measured reflection coefficient (S11) shows a 50.25% bandwidth in the lower band (from 2.119 to 3.058 GHz) and 4.27% in the upper band (from 5.058 to 5.276 GHz). Radiation efficiency obtained in the lower and upper band are >95 and 80%, respectively.